UJI VIABILITAS POLEN KAKAO (Theobroma cacao L.) SETELAH PRESERVASI - , ZUNISNAINI; , Prof. Dr. Issirep Sumardi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cocoa (Theobroma cacao L.) is a cauliflorous tree with abundant flowers. The intensity of pollination determines the amount of fruit production. The proportion of flower giving rise to mature pods is 5% from 10% natural pollinated flower because of pollination incompatibility. The breeding of cocoa needs to be done by artificial pollination because the period of pollination is very short, so the percentage of flower that develop into mature fruit is smaller than the number of pollinated flower. Artificial pollination requires large numbers of viable pollen, therefore it is necessary to preserved pollen as pollen bank that is ready for use at any time. The purposes of this study were: 1) to know the method of pollen preservation, which effective and efficient way, so that the viability are remained high, 2) to study the receptivity of stigma after pollinated with storage pollen. This research used pollen from three clones of cocoa with self-compatible (KW 163), partially self-compatible (ICS 60) dan self-incompatible (Na 32) compatibility type. The method was used for pollen storage is the freeze-drying. Pollen was collected and placed in a capsule inserted in the flacon bottle for storage treatment. Glass jars containing flacon bottles was stored in a freezer (-20Â° C), the refrigerator at (4Â° C), and stored at the desiccators (room temperature) for 2 weeks. To know the stigma receptivity, hand pollination was done. Pollen collection, storage, pollen viability test and stigma receptivity test was done at the Center for Indonesian Coffee and Cocoa Research Institute in Jember. The slide preparation of pistil was done in Laboratory of Plant Structure and Development, Faculty of Biology, Gadjah Mada University. Data of pollen viability were analyzed by ANOVA continued by 5% LSD (Least Significant Difference) test. The stigma receptivity after pollinated with storage pollen was analyzed descriptively. The statistical analysis result showed that 2 weeks after storage in freezer had the highest viability (92,71%) and significant differ compared with the refrigerator (89,02%) and desiccators (85,98%) treatments after acetocarmine test and in vitro culture. The stigma receptivity analysis result after microscopy test from the three ovarium clones were used, showed that there are tissues development after fertilization, proved that stigma still receptive after pollinated with storage pollen.